Cardiovascular risk assessment in people living with HIV compared to the general population. (14th October 2021) - Delabays, B; Cavassini, M; Damas Fernandez, J; Beuret, H; Calmy, A; Hasse, B; Bucher, H; Frischknecht, M; Vollenweider, P; Marques-Vidal, P; Vaucher, J
Abstract: Background: Effective cardiovascular preventive strategies are crucial among people living with HIV (PLWH), who are facing a high burden of atherosclerotic cardiovascular disease (ASCVD). However, it remains unclear which cardiovascular risk score is the most appropriate in clinical practice. Purpose: We aimed to prospectively assess and compare the accuracy of widely used cardiovascular risk scores in PLWH and individuals from the general population. Methods: We used data from the Swiss HIV Cohort Study (SHCS), a longitudinal study involving 20, 802 HIV-infected adults aged over 18 years, and from the CoLaus|PsyCoLaus study, a Swiss population-based cohort including 6, 733 individuals aged 35–75 years. The European Systematic Coronary Risk Evaluation Score (SCORE), the North American Pooled Cohort Equation (PCE) and the HIV-specific Data Collection o-n Adverse events of Anti-HIV Drugs (D:A:D) score were calculated for all participants free from ASCVD between January 1, 2003 and December 31, 2009. Accuracy of the scores was assessed based on discrimination and calibration metrics for each cohort separately using incident ASCVD as outcome. The value of adding HIV-specific factors to the model presenting the best predictive capacities between SCORE and PCE was evaluated using the net reclassification index (NRI). Results: 6, 373 PLWH (28.4% women; aged 40.6 [SD, 9.9]; 57.2% on antiretroviral therapy) and 5, 403 individuals from the general population (53.5% women, aged 52.8 [SD, 10.7]) were included in the analysis with a mean follow-up time of 13.5 (SD, 4.1) and 9.9 (SD, 2.3) years, respectively. 533 (8.4%) participants in the SHCS and 374 (6.9%) in the CoLaus|PsyCoLaus study experienced an incident ASCVD translating into age-adjusted incidence rates of 12.9 vs. 7.5 per 1, 000 person-year, respectively. In SHCS, PCE and D:A:D presented discriminative capacities with AUROC of 0.757 (95% CI, 0.736–0.777) and 0.763 (95% CI, 0.743–0.783), respectively, compared to SCORE (0.704 [95% CI, 0.681–0.728]). Calibration of all scores was suboptimal in SHCS, with under-prediction of ASCVD in the higher deciles of risk compared to the CoLaus|PsyCoLaus study. Adding CD4 nadir (<200 cells/mm 3 ) and abacavir exposure as categorical variables to PCE resulted in a marginal improvement in discrimination and in a global NRI of 2.7% (95% CI, 0.3–5.1, p-value = 0.03). Conclusions: PLWH presented a two-fold higher rate of incident ASCVD compared to individuals of the same age from the general population. The accuracy of PCE score to predict ASCVD in PLWH is equivalent to the D:A:D score and may represent a better alternative due to its reduced set of variables and its widespread use. Adding HIV-specific factors to PCE did not improve its predictive performance. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation